2017
DOI: 10.4103/sja.sja_624_16
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dexmedetomidine as an adjuvant to bupivacaine in femoral nerve block for perioperative analgesia in patients undergoing total knee replacement arthroplasty: A dose–response study

Abstract: Context:Dexmedetomidine is being increasingly used in nerve blocks. However, there are only a few dose determination studies.Aims:To compare two doses of dexmedetomidine, in femoral nerve block, for postoperative analgesia after total knee arthroplasty (TKA).Settings and Design:A prospective, randomized, controlled trial was conducted in the Department of Anesthesia at AIIMS, a Tertiary Care Hospital.Materials and Methods:Sixty American Society of Anesthesiologists I–II patients undergoing TKA under subarachno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(50 citation statements)
references
References 22 publications
(28 reference statements)
2
46
1
1
Order By: Relevance
“…Our results are also comparable to the results of Packiasabapathy et al [16], who assessed the effect of dexmedetomidine as an adjuvant to bupivacaine in showed that there was no statistically significant difference between both groups regarding the total intraoperative complications femoral nerve block for perioperative analgesia in patients undergoing total knee replacement arthroplasty. They demonstrated that the addition of 100 μg dexmedetomidine to 0.5% bupivacaine was associated with a prolonged duration of analgesia, and lower pain score at rest.…”
Section: Time Of Measurementsupporting
confidence: 89%
“…Our results are also comparable to the results of Packiasabapathy et al [16], who assessed the effect of dexmedetomidine as an adjuvant to bupivacaine in showed that there was no statistically significant difference between both groups regarding the total intraoperative complications femoral nerve block for perioperative analgesia in patients undergoing total knee replacement arthroplasty. They demonstrated that the addition of 100 μg dexmedetomidine to 0.5% bupivacaine was associated with a prolonged duration of analgesia, and lower pain score at rest.…”
Section: Time Of Measurementsupporting
confidence: 89%
“…The initial literature search identi ed 143 articles, of which 135 were excluded because they failed to meet the eligibility criteria or were duplicates. A total of 7 RCTs involving 546 participants were nally included in this meta-analysis (8)(9)(10)(11)(12)(13)(14). The PRISMA ow diagram is presented in Fig 1. The evidence quality and risk assessment were evaluated according to the Cochrane Collaboration's tool for assessing risk of bias.…”
Section: Search Results and Risk Assessmentmentioning
confidence: 99%
“…Total opioids consumption was recorded in 4 studies (8,9,11,12) containing patients. Pooled data indicated that there were signi cant differences between these two groups (SMD = -0.63[-0.86 to -0.40], P<0.01, I 2 = 0%, Fig 5).…”
Section: Total Opioids Consumption In 24 Hours Postoperativelymentioning
confidence: 99%
See 1 more Smart Citation
“…Todos los trabajos analizados en este subgrupo se realizaron en mayores de 18 años, ASA I-II y con fin último como analgesia para cirugía traumatológica de rodilla o tobillo (Tabla II) (8,39-43). En este apartado es difícil poder establecer una relación directa entre la dosificación de la DEX perineural y la duración de la analgesia tras el bloqueo, pues de los trabajos analizados, en 4 se utilizó de manera concomitante anestesia neuroaxial o general, dado ello, el tipo, concentración y volumen de AL usado posteriormente fue muy variado (0,125-0,5 % 20-40 ml), sumado al hecho de que en algunos de los ensayos se instaló un catéter para bloqueo continuo de nervio periférico, dificultando aún más el poder establecer una correlación tan exacta entre la DEX perineural y el primer requerimiento de analgesia solicitado por paciente (8,39-43).En términos objetivos, observamos que al utilizar DEX perineural (en dosificación 0,5-2 µg/kg), con AL de larga duración, sin otros coadyuvantes, en bloqueos de extremidad inferior (nervio femoral, ciático y/o safeno), la latencia del bloqueo se redujo en promedio un 41,42 % (15,20 a 8,90 minutos), la duración de la analgesia aumentó en promedio un 67,84 % (487,18 a 834,47 minutos) y la duración del bloqueo motor aumentó en promedio un 107 % (545,00 a 1132,25 minutos), sin embargo, debemos recordar al interpretar estos resultados, sobre todo con respecto al bloqueo motor, que se usó inicialmente anestesia espinal y/o catéter de bloqueo continuo en varios de los trabajos analizados(40)(41)(42)(43).DEXMEDETOMIDINA Y BLOQUEOS CENTRALESExiste muy poca información disponible con respecto al rendimiento de la DEX perineural adicionado a AL en bloqueos centrales de tronco, no encontrando a la fecha, y en base a la metodología utilizada, más allá de 10-12 ensayos clínicos al respecto. La Tabla III resume los estudios encontrados en base a los criterios metodológicos establecidos(44)(45)(46)(47).…”
unclassified